First record of the weevil genus Pseudanthonomus Dietz (Coleoptera: curculionidae) from Mexican amber - Legalov, Andrei A. (Paleontological journal)
A new species, weevil Pseudanthonomus antonkozlovi sp. nov., from Early Miocene Mexican amber is described and illustrated. The new species differs from P. rufulus Dietz, 1891 from Canada and USA in the larger body size, long rostrum, and wider femora. It is the first fossil record of the genus Pseudanthonomus and the second representative of the tribe Anthonomini described from Mexican amber.